AQUIFER CHARACTERISTICS OF SOME LOCAL GOVERNMENT AREAS OF BENUE STATE, NIGERIA (Nigerian Journal of Technology, 2018)
Well pumping test results from 74 boreholes within twelve LGAs of Benue State were collated and analysed to determine the aquifer hydraulic characteristics. Cooper-Jacobâ€™s non-uniform flow equation was used to determine the transmissivity, T, storativity, S, hydraulic conductivity, K and specific capacity, Sc of the aquifers of the study areas. The Geographical Information System (GIS) was used to generate colour coded maps of the determined hydraulics characteristics of the aquifers. The static water level (SWL) ranged from 2 to 8 m in Katsina-Ala, Ado, parts of Vandeikya and Gboko, while the rest of the study areas had SWL of 8 to 20 m with isolated areas of Konshisha and Gboko having SWL up to 38 m. Hydraulic conductivity values fall between 0.01 to 1.0 m/day in most of the study areas except Gboko and Buruku LGAs where K ranged between 1.0 to 5.0 m/day. The specific capacity of major parts of the study areas ranged from 0.01 to 10 m2/day except Konshisha, Gboko and Ushongo LGAs where the values ranged from 10.0 to 50.0 m2/day with the highest value of 83 m2/day obtained at Tse-Filla in Konshisha LGA. Transmissivity values ranged from 0.01 to 8 m2/day except, parts of Konshisha and Gboko where the value went up to 16 m2/day and 49 m2/day respectively. The highest value of storativity was 2.4 in Ado LGA with a range of 0.4 to 1.0 in parts of Katsina-Ala, Ukum, Konshisha, Ushongo and Gboko LGAs. The remaining parts of the study area had storativity values of 0.01 to 0.4. The results show that the aquifers of the study areas are of moderate to low or limited yield. The generated hydraulic characteristics are useful tools for planning and development of ground water in the study area. Keywords: Aquifer characteristics, non-uniform equation, pumping test, ground water. http://dx.doi.org/10.4314/njt.v38i1.28